Hubungan Hipertensi Terhadap Kejadian Stroke - Puti Nadhirah Puspitasari (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Stroke is defined as a disruption in the blood supply to the brain. Many factors can affect the incidence of stroke. Hypertension is the main triggering factor of stroke, both hemorrhagic and ischemic strokes. Objective: To find out more about the relationship of hypertension to the incidence of stroke. Methods: The method used is a literature study taken from various national and international journals, this method always tries to meet the latest conditions on a topic.Conclusion: There is a relationship of hypertension with the incidence of stroke